A versatile method for the preparation of ferroelectric supramolecular materials via radical end-functionalization of vinylidene fluoride oligomers - García-Iglesias, Miguel; de Waal, Bas F. M.; Gorbunov, Andrey V.; Palmans, Anja R. A.; Kemerink, Martijn; Meijer, E. W. (Journal of the American Chemical Society, 2016)
A synthetic method for the end-functionalization of vinylidene fluoride oligomers (OVDF) via a radical reaction between terminal olefins and I-OVDF is described. The method shows a wide substrate scope and excellent conversions, and permits the preparation of different disc-shaped cores such as benzene-1,3,5-tricarboxamides (BTAs), perylenes bisimide (PBI), and phthalocyanines (Pc) bearing three to eight ferroelectric oligomers at their periphery. The formation, purity, OVDF conformation, and morphology of the final adducts has been assessed by a combination of techniques, such as NMR, size exclusion chromatography, differential scanning calorimetry, polarized optical microscopy, and atomic force microscopy. Finally, PBI-OVDF and Pc-OVDF materials show ferroelectric hysteresis behavior together with high remnant polarizations, with values as high as Pr ≈ 37 mC/m2 for Pc-OVDF. This work demonstrates the potential of preparing a new set of ferroelectric materials simply by attaching OVDF oligomers to different small molecules. The use of carefully chosen small molecules paves the way to new functional materials in which ferroelectricity and electrical conductivity or light-harvesting properties coexist in a single compound.